Índice de espiralamento do cordão umbilical e possível repercussão nos resultados perinatais imediatos - Naidon, Débora (2013)
The umbilical cord, the most important connection between fetus and placenta, which is re-sponsible for the development and maintenance of the intrauterine life, consists of a spiral structure whose blood vessels carry nutrients from mother to fetus, and catabolites from fetus to mother. Studies on number of coiling on the umbilical cord have not been relevant in the current literature. In other words, this funicular parameter is undervalued by the specialist medical community. However, some studies show an association between umbilical cord coiling and adverse perinatal outcomes. This is an analytical cross-sectional study aimed to assess the umbilical cord coiling index (UCI) during the postpartum period, and relate the UCI with perinatal outcomes in pregnant women admitted to have their births at HUSM, from June to October, 2012. A coil was defined as a complete 360 degree spiral course of the umbilical vessels around the Wharton s jelly. The UCI was defined by being the relation between the number of spirals and the length of the cord, and the values found between the 10th and 90th percentile were considered as within the limits of normality. For values under P10, the umbilical cord was hypocoiled and over P90, hypercoiled. Two hundred fifty two placentas and their cords were evaluated, but 179 births were considered for the analysis of perinatal outcomes. The average UCI was 0.17 ± 0.86 coils/cm while the hypocoiling (UCI<0.05 coils/cm) and hypercoiling (UCI> 0.28 coils/cm) represented 8.4% (n = 21) and 8.8% (n = 22) respectively. There was a significant correla-tion between the UCI and the Apgar score at 1 and 5 minute (p <0.05). Among preterm newborns, 26.3% had abnormal coiling. Among small for gestational age (SGA) 26,6% had abnormal coiling too. Only one death occurred in utero and the umbilical cord was hypercoiled (UCI = 0.42 coils/cm). There was no correlation or association between the IEC and other perinatal outcomes, such as meco-nium staining amniotic fluid, fetal distress, intrauterine growth restriction (IUGR), neonatal intensive care unit (NICU) admission and neonatal death. The results allow to conclude that the UCI can relate to adverse perinatal outcomes, although few of them in this study had statistical significance, which may be attributed to the sample size, addressing the need for further study on the subject.